2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6092008
|View full text |Cite
|
Sign up to set email alerts
|

A detailed 3D ankle-foot model for simulate dynamics of lower limb orthosis

Abstract: The objective of this study is to develop a 3D ankle-foot model containing toe expression for designing an AFO (ankle-foot orthosis) with a training function. Two experiments were conducted to (1) show the influence of toes by comparing walking with and without an AFO, and (2) clarify the functions of toes during walking by correlating the activity of the major muscles controlling the ankle and the toes to the sole pressure data during walking. By analyzing the results of these two experiments, the necessary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The MP joint is rarely used to measure gait.However, the importance of the toes in stabilizing the body during walking has been reported in various studies [11,12], and we wished to ascertain the relevance of the toes to electromyography (EMG) of the foot. We have previously discussed the influence of AFOs on the MP joint [13]. By analyzing pressure on the sole during walking with and without an AFO, it was found that load is applied more lightly to the forefoot when an AFO is worn.…”
Section: Introductionmentioning
confidence: 97%
“…The MP joint is rarely used to measure gait.However, the importance of the toes in stabilizing the body during walking has been reported in various studies [11,12], and we wished to ascertain the relevance of the toes to electromyography (EMG) of the foot. We have previously discussed the influence of AFOs on the MP joint [13]. By analyzing pressure on the sole during walking with and without an AFO, it was found that load is applied more lightly to the forefoot when an AFO is worn.…”
Section: Introductionmentioning
confidence: 97%